Pilot study of vincristine, oral irinotecan, and temozolomide (VOIT regimen) combined with bevacizumab in pediatric patients with recurrent solid tumors or brain tumors. Issue 9 (29th April 2013) - Wagner, Lars; Turpin, Brian; Nagarajan, Rajaram; Weiss, Brian; Cripe, Timothy; Geller, James
Abstract Background The combination of vincristine, oral irinotecan, and temozolomide (VOIT regimen) has shown antitumor activity in a pediatric Phase I trial. To further potentiate synergy, we assessed the safety and feasibility of adding bevacizumab to VOIT for children and young adults with recurrent tumors. Methods Patients received vincristine (1.5 mg/m2 on day 1), oral irinotecan (90 mg/m2 on days 1–5), temozolomide (100–150 mg/m2 on days 1–5), and bevacizumab (15 mg/kg on day 1) in 3‐week cycles, which were repeated for up to six cycles. Cefixime prophylaxis was used to reduce irinotecan‐associated diarrhea. Results Thirteen patients received 36 total cycles. Six of the first 10 patients required dose reductions due to toxicity during the first cycle (n = 3) or subsequent cycles (n = 3), and these grade 3 side effects included prolonged nausea, dehydration, anorexia, neuropathy, diarrhea, and abdominal pain, as well as prolonged grade 4 neutropenia. After reducing daily temozolomide to 100 mg/m2, three additional patients tolerated therapy well without the need for dose reductions. Toxicities attributed to bevacizumab were limited to grade 1 epistaxis (1) and grade 2 proteinuria (1). Tumor responses were seen in both patients with Ewing sarcoma. Conclusions Reducing temozolomide from 150 to 100 mg/m2/day improved tolerability, and treatment with this lower temozolomide dose was feasible and convenient as outpatient therapy. Although responses were seen in Ewing sarcoma, the benefit of adding bevacizumab remains unclear. Pediatr Blood Cancer 2013;60:1447–1451. © 2013 Wiley Periodicals, Inc.